Bicarbonate activates glycolysis and lactate production in corneal endothelial cells by increased pHi. (October 2020) - Li, Shimin; Shyam, Rajalekshmy; Ogando, Diego G.; Bonanno, Joseph A.
Abstract: Recent studies have shown that lactate coupled water flux is the underlying mechanism of the corneal endothelial pump, which is highly dependent on the presence of bicarbonate. In this study we test the hypothesis that the increased intracellular pH (pHi ) caused by bicarbonate stimulates glycolytic activity and the production of lactate by endothelial cells. Primary cultures of bovine corneal endothelial cells (BCEC) were incubated in bicarbonate-free (BF) ringer, a high [HEPES] ringer, and bicarbonate-rich (BR) ringer all at pH 7.5. Lactate production and glucose consumption were greatest in BR>HEPES >BF. Similarly, pHi was greatest in BR>HEPES>BF. Increasing pHi with NH4 Cl also increased lactate production in BF or BR, indicating that the increased lactate production in BR is not due to HCO3 − itself. Glucose transport capacity, as measured by 2-N-(7-Nitrobenz-2-oxa-1, 3-diazol-4-yl)Amino-2-Deoxyglucose (2-NBDG) uptake was unaffected by the three incubation conditions. Using Laconic, a FRET sensor for lactate, we found that intracellular [lactate] increased immediately and transiently when cells were switched from BF to BR perfusion indicating increased lactate production with subsequent matching of efflux. Moreover, induction of acute lactate influx by perfusion pulses of 10 mM lactate increased intracellular [lactate] significantly faster in BF than in BR, consistent with higher lactate production and efflux in BR. In summary, our results indicate that glycolytic flux and lactate production increase in BR due to increased pHi, consistent with the well-known pH sensitivity of phosphofructokinase, the rate limiting enzyme in glycolysis. Highlights: Effect of Bicarbonate-free vs Bicarbonate-Rich Ringer on Corneal Endothelial Lactate Production. Increased pHi in Bicarbonate. Intracellular Lactate Measurement by Laconic. Bicarbonate Rich Ringer Accelerates Lactate Production.